Empirical evidence for metabolic drift in plant and algal lipid biosynthesis pathways - Zonnequin, Maëlle; Belcour, Arnaud; Delage, Ludovic; Siegel, Anne; Blanquart, Samuel; Leblanc, Catherine; Markov, Gabriel V. (Frontiers in Plant Science, 2024)
Metabolic pathway drift has been formulated as a general principle to help in the interpretation of comparative analyses between biosynthesis pathways. Indeed, such analyses often indicate substantial differences, even in widespread pathways that are sometimes believed to be conserved. Here, our purpose is to check how much this interpretation fits to empirical data gathered in the field of plant and algal biosynthesis pathways. After examining several examples representative of the diversity of lipid biosynthesis pathways, we explain why it is important to compare closely related species to gain a better understanding of this phenomenon. Furthermore, this comparative approach brings us to the question of how much biotic interactions are responsible for shaping this metabolic plasticity. We end up introducing some model systems that may be promising for further exploration of this question.